2016
DOI: 10.1002/brb3.427
|View full text |Cite
|
Sign up to set email alerts
|

High‐gamma power changes after cognitive intervention: preliminary results from twenty‐one senior adult subjects

Abstract: IntroductionBrain‐imaging techniques have begun to be popular in evaluating the effectiveness of cognitive intervention training. Although gamma activities are rarely used as an index of training effects, they have several characteristics that suggest their potential suitability for this purpose. This pilot study examined whether cognitive training in elderly people affected the high‐gamma activity associated with attentional processing and whether high‐gamma power changes were related to changes in behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…Although Mozolic et al (2010) did not observe any structural changes after 8 hours of training, training-related functional increases in cerebral blood flow were found. Similarly, significant increases in frontal activation were observed in two other studies after 8 hours of cognitive training (Akimoto et al, 2016;Gaál and Czigler, 2018). Decreased frontal and parietal activation was observed after 9 to 12 hours training (Brehmer et al, 2011;Heinzel et al, 2016;Kühn et al, 2017), and increased activation in subcortical regions after 10 hours training (Brehmer et al, 2011).…”
Section: Qualitative Examination Of Characteristics Moderating Functisupporting
confidence: 62%
See 4 more Smart Citations
“…Although Mozolic et al (2010) did not observe any structural changes after 8 hours of training, training-related functional increases in cerebral blood flow were found. Similarly, significant increases in frontal activation were observed in two other studies after 8 hours of cognitive training (Akimoto et al, 2016;Gaál and Czigler, 2018). Decreased frontal and parietal activation was observed after 9 to 12 hours training (Brehmer et al, 2011;Heinzel et al, 2016;Kühn et al, 2017), and increased activation in subcortical regions after 10 hours training (Brehmer et al, 2011).…”
Section: Qualitative Examination Of Characteristics Moderating Functisupporting
confidence: 62%
“…Exploration of training dose indicated that 8 hours of multidomain training did not promote transfer (Akimoto et al, 2016). However, studies employing 8 hours of singledomain training demonstrated cognitive transfer, though improvements were limited and generally restricted to trained and near-transfer tasks (Gaál and Czigler, 2018;Mozolic et al, 2010).…”
Section: Qualitative Examination Of Characteristics Moderating Cognitmentioning
confidence: 99%
See 3 more Smart Citations